Aromatic alkyne insertion into six-membered cyclometalated pyridine complexes of iridium: different insertion modes and structurally novel products. Issue 13 (14th February 2018) - Chu, Xiaodan; Zhang, Shaowei; Wang, Zhuo; Li, Tongyu; Zhu, Bolin
Abstract : Insertion reactions of aromatic alkynes into the Ir–C bond of six-membered cycloiridated complexes formed various novel products via different insertion modes. Abstract : Reactions of 2-benzoylpyridine or 2-benzylpyridine with [Cp*MCl2 ]2 (M = Ir, Rh) have been carried out in the presence of NaOAc in refluxing methanol, which form the corresponding six-membered cyclometalated products (1–3 ) except for the reaction of 2-benzylpyridine with [Cp*RhCl2 ]2 . Insertion reactions of two six-membered cyclometalated pyridine iridium complexes (1 and2 ) with terminal or internal aromatic alkynes were studied. Terminal alkynes p -XC6 H4 CCH (X = H, MeO, and F) with1 give the corresponding five- and seven-membered doubly cycloiridated complexes4a–c, internal alkynes p -XC6 H4 CCC6 H4 X- p (X = H, MeO, and Br) form the similar five- and seven-membered doubly cycloiridated complexes (5a, b ) and/or di-insertion products (6a, c ), whereas the acyl alkyne PhCCCOPh affords the novel spiro-metalated complex7 . For complex2, internal alkynes p -XC6 H4 CCC6 H4 X- p (X = H, MeO, and Br) form similar five- and seven-membered doubly cycloiridated complexes (8a–c ). However, in the case of PhCCCOPh, the reaction gives the novel four-membered cyclometalated complex9 . These results suggest that the products formed by alkyne insertion reactions of the six-membered cycloiridated pyridine complexes are very diverse. Plausible pathways for the formation of these novel insertion products were proposed. Molecular structures of seven cyclometalated complexes were determined by X-ray diffraction.